Audit on maternal mortality in a tertiary care centre in India of 6 years, a retrospective analysis - Agrawal, Neha; Chaudhari, Hemangi K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: This study is carried out on 382 cases of maternal deaths from July 2010 to June 2016 at the department of obstetrics and gynaecology of tertiary centre to evaluate causes and risk factor associated with maternal deaths. Methods: Retrospective analysis of all maternal deaths occurred in department of obstetrics and gynaecology of tertiary care hospital from July 2010 to June 2016. Results: The MMR in the study period was 915/100000 live births. Maximum no. of maternal death 42.7% were in age group of 21-25 years, majority of them residing in urban area. 117 patients referred from sub-district/district hospital. 76.4% patients were registered. 60% maternal deaths were seen in postnatal period. In present study majority of maternal deaths 60% were due to indirect cause while 40% patients died due to direct cause. Major causes of maternal deaths were hypertensive disorder 12%, obstetric haemorrhage 11% tuberculosis 11%, hepatitis E 8% and pregnancy related infections 5.6%. Conclusions: High maternal mortality can be due to the fact that the study was conducted in tertiary care referral centre. Referral of moribund cases from rural, sub-district, district and peripheral hospital to our institute have inflated this mortality ratio. All of these being preventable causes of death can be avoided by improving standard of obstetric care, increasing number of health professionals, upgradation of healthcare facilities at first referral units and by making better health policies.